Simulation of Heat and Mass Transfer of Cocoa Beans under Stepwise Drying Conditions in a Heat Pump Dryer - Hii, C.; Law, C.; Law, Ming (Elsevier, 2013)
The present study investigated the kinetics of heat pump drying of cocoa beans under stepwise drying conditions and the heat and mass transfer analysis carried out using 3-D computer simulation. The fermented cocoa beans were subject to drying at constant temperature (56 C), step up temperature (30.7 Ce43.6Ce56.9 C) and step down temperature (54.9 Ce43.9 C) drying profiles. Shrinkage factor was incorporated into the heat and mass transfer models. Simulation results showed that the mean relative errors determined ranged from 3.1% to 12.1% in the predicted moisture ratio profiles in both models with and without shrinkage factor. In the bean temperature profiles, results showed excellent agreement between the predicted and experimental data with mean relative errors less than 5%. The present study showed that shrinkage played a lesser role in the analysis due to the small shrinkage ratio observed before and after drying.